Thoughts on the Postpartum Situation - Scuro, Jennifer (Frontiers in Sociology, 2018)
The event of childbirth carries with it a dominant narrative: that a pregnant woman happily gives birth to a baby. This appears to be quite a simple formulation – as if a natural fact, as if plain and common sense. Yet, the complexities masked by the mythological and whitewashed quality of this narrative, as I have already argued recently in my graphic novel narrative/philosophical analysis, The Pregnancy ≠ Childbearing Project: A Phenomenology of Miscarriage (2017), harms and even kills women. In this paper, I expand on the problem of what I term ‘dismemberment after birth’ as operates invisibly in the ‘postpartum situation.’ The dominant narrative, combined with a pervasive cultural misogynoir as well as medicalized and ableist establishment of care, renders women without resource if they cannot maintain the desires and embodiments required of a contented and successful maternity. The naturalized assumptions about the narrative move from the birth event to ‘having a baby’ are disrupted here with hope of opening up an opportunity to validate and diversify the more non-linear narratives. As an afterthought to these disruptions I present here, I offer an additional challenge to anti-natalist thinking in its limited insight into the postpartum situation.